2018
DOI: 10.4196/kjpp.2018.22.6.689
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-glucoside inhibits amyloid β25–35-induced neuronal cell death in cultured rat hippocampal neurons

Abstract: Increasing evidence implicates changes in [Ca2+]i and oxidative stress as causative factors in amyloid beta (Aβ)-induced neuronal cell death. Cyanidin-3-glucoside (C3G), a component of anthocyanin, has been reported to protect against glutamate-induced neuronal cell death by inhibiting Ca2+ and Zn2+ signaling. The present study aimed to determine whether C3G exerts a protective effect against Aβ25–35-induced neuronal cell death in cultured rat hippocampal neurons from embryonic day 17 fetal Sprague-Dawley rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…C3G is protective against glutamate-induced neuronal cell death [ 20 ] and ischemia-induced neuronal cell death [ 21 , 22 ]. It can prevent ethanol neurotoxicity [ 23 ] and can protect against amyloid β(Aβ)-induced cytotoxicity [ 23 , 24 , 25 ]. It can also promote the inhibition of Aβ (Aβ40, Aβ1-42) fibrillization and protect neuronal cells from Aβ1-42, Aβ40, and Aβ25-35 induced cytotoxicity [ 6 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C3G is protective against glutamate-induced neuronal cell death [ 20 ] and ischemia-induced neuronal cell death [ 21 , 22 ]. It can prevent ethanol neurotoxicity [ 23 ] and can protect against amyloid β(Aβ)-induced cytotoxicity [ 23 , 24 , 25 ]. It can also promote the inhibition of Aβ (Aβ40, Aβ1-42) fibrillization and protect neuronal cells from Aβ1-42, Aβ40, and Aβ25-35 induced cytotoxicity [ 6 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can prevent ethanol neurotoxicity [ 23 ] and can protect against amyloid β(Aβ)-induced cytotoxicity [ 23 , 24 , 25 ]. It can also promote the inhibition of Aβ (Aβ40, Aβ1-42) fibrillization and protect neuronal cells from Aβ1-42, Aβ40, and Aβ25-35 induced cytotoxicity [ 6 , 24 , 25 , 26 , 27 ]. In rats, C3G can prevent the cognitive impairment induced by Aβ [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, exposure of primary hippocampal neurons to 20 μM Aβ 25–35 for 24 h significantly decreased neuronal viability and increased the intracellular Zn 2+ concentration, whereas TPEN, a membrane-permeable Zn 2+ -specific chelator, attenuated Aβ 25–35 -induced neuronal death and reversed Aβ 25–35 -induced intracellular Zn 2+ concentration increase. Coincidentally, Yang et al recently reported that treatment with Aβ 25–35 increased intracellular Zn 2+ , then might cause mitochondrial depolarization, formation of ROS, the activation of caspase-3, and neuron damage in cultured rat hippocampal neurons, also suggesting synergy neurotoxic effects of intracellular Zn 2+ and amyloid beta [ 53 ]. Taken together, intracellular Zn 2+ dysregulation mediated the neurotoxicity of Aβ 25–35 , and it may be an effective strategy for preventing Aβ-induced neuronal damage by capturing Zn 2+ released from intracellular Zn-Aβ complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity of compound 2 was evaluated using an MTT assay. 32 First, compound 2 was dissolved in DMSO. Then, it was dissolved in the free medium immediately before being used for cell treatment and was followed by 70% sonication and ltration of the material through a 0.45-µM lter (Millipore, Billerica, MA, USA).…”
Section: Mtt Assaymentioning
confidence: 99%